Multi-layer topological transmissions of spoof surface plasmon polaritons - Pan, Bai Cao (Sci Rep, 2016)
Spoof surface plasmon polaritons (SPPs) in microwave frequency provide a high field confinement in subwavelength scale and low-loss and flexible transmissions, which have been widely used in novel transmission waveguides and functional devices. To play more important roles in modern integrated circuits and systems, it is necessary and helpful for the SPP modes to propagate among different layers of devices and chips. Owing to the highly confined property and organized near-field distribution, we show that the spoof SPPs could be easily transmitted from one layer into another layer via metallic holes and arc-shaped transitions. Such designs are suitable for both the ultrathin and flexible single-strip SPP waveguide and double-strip SPP waveguide for active SPP devices. Numerical simulations and experimental results demonstrate the broadband and high-efficiency multi-layer topological transmissions with controllable absorption that is related to the superposition area of corrugated metallic strips. The transmission coefficient of single-strip SPP waveguide is no worse than −0.8 dB within frequency band from 2.67 GHz to 10.2 GHz while the transmission of double-strip SPP waveguide keeps above −1 dB within frequency band from 2.26 GHz to 11.8 GHz. The proposed method will enhance the realizations of highly complicated plasmonic integrated circuits.